2010
DOI: 10.1007/s00421-010-1601-9
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual variability in the adaptation of human muscle specific tension to progressive resistance training

Abstract: Considerable variation exists between people in the muscle response to resistance training, but there are numerous ways muscle might adapt to overload that might explain this variable response. Therefore, the aim of this study was to quantify the range of responses concerning the training-induced change in maximum voluntary contraction (MVC) knee joint torque, quadriceps femoris (QF) maximum muscle force (F), physiological cross-sectional area (PCSA) and specific tension (F/PCSA). It was hypothesized that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 57 publications
9
94
2
2
Order By: Relevance
“…Similar inter-individual variation has been observed also previously in muscle strength responses to RT (Erskine et al 2010). Additionally, aging did not influence the present changes in muscle strength although a sarcopenic phenotype (i.e., lower muscle strength per body mass, see Table 1) was observed in older subjects.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar inter-individual variation has been observed also previously in muscle strength responses to RT (Erskine et al 2010). Additionally, aging did not influence the present changes in muscle strength although a sarcopenic phenotype (i.e., lower muscle strength per body mass, see Table 1) was observed in older subjects.…”
Section: Discussionsupporting
confidence: 90%
“…The confidence intervals (CI) of changes in muscle size and strength in the control group were determined by Univariate GLM, and the upper 95 % CI was used as the lower limit for a significant individual training-induced change in the training group (Hopkins 2000;Karavirta et al 2011b). Individuals with gains in muscle size and strength beyond 1 SD from the mean of the training group were defined as high responders (Erskine et al 2010). Statistical significance was accepted when p ≤ 0.05.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the individual changes in strength following training and the putative underpinning neural and morphological adaptations has previously been investigated primarily using bivariate correlations. These studies have reported changes in strength to be both significantly related and unrelated to the changes in neural [significant: agonist electromyography (EMG): r = 0.66-0.74 (Häkkinen et al 1985;Häkkinen and Komi 1986;Shima et al 2002); non-significant: agonist activation assessed with the interpolated twitch technique (ITT): r = −0.124-0.47 (Erskine et al 2010b), antagonist EMG: r = 0.09 (Erskine et al 2010b) or morphological variables [significant: muscle volume assessed via magnetic resonance imaging (MRI): r = 0.48-0.53 (Erskine et al 2014); non-significant: muscle volume assessed via MRI: r = 0.15 (Erskine et al 2010b); muscle fascicle pennation angle (θ p ) assessed via ultrasonography: r = −0.33-0.26 (Nimphius et al 2012)]. Therefore, there is considerable confusion about the contribution of specific physiological variables to the individual changes in strength.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have examined two or more predictor variables to assess neural and morphological factors, typically finding only one variable to make a significant contribution to the explained variance (Erskine et al 2010b(Erskine et al , 2014, negating the need for a more comprehensive multi-factorial analysis. The exception is Higbie et al (1996) who found a remarkable 65% of the variability in concentric strength gains to be due to the combination of neural (agonist activation assessed with EMG) and hypertrophic (muscle cross-sectional area) adaptations.…”
Section: Introductionmentioning
confidence: 99%